Um estudo sobre a circulação de notícias envolvendo a facada em Jair Bolsonaro - Nascimento, Amanda do (2020)
Twitter users act as active audience of journalistic products published by major media outlets, such as G1, Folha de São Paulo and Estado de São Paulo. In this article, we analyzed three tweets, one from each newspaper, in which informs the episode of the stab at the presidential candidate Jair Bolsonaro. Initially, all responses to the tweets were classified and evaluated individually, and then together, to understand the reason for each comment and what the predominant meanings in the circulation of these journalistic contents.